Sustainable business practice and going concern of selected listed manufacturing companies in Nigeria - Boluwaji, Olayinka Dominion; Igbekoyi, Olusola Esther; Dagunduro, Muyiwa Emmanuel; Busayo, Temitayo Oluwatimilehin; Osatuyi, Ogunyemi Abraham (International Journal of Emerging Trends in Social Sciences, 2024)
Sustainability has become a crucial aspect of modern business, extending beyond corporate social responsibility to form an integral part of organizational strategies. This study investigated how sustainable business practices impact the going concern of listed manufacturing companies in Nigeria, focusing on stakeholder inclusiveness, dynamic workplace, and community engagement. The research used an ex-post facto research design, analyzing data from 60 consumer and industrial goods manufacturing companies listed on the Nigerian exchange group as of December 31, 2021. The findings indicated that stakeholder inclusiveness, a dynamic workplace, and community engagement positively and significantly influence the net asset per share of these listed manufacturing companies. In other words, incorporating sustainable business practices can enhance the companies’ long-term financial stability and operational continuity. In conclusion, this study emphasizes the potential of sustainable business practices to shape the going concern status of listed manufacturing companies in Nigeria when effectively implemented. It suggests that manufacturing companies should develop and implement a well-balanced sustainability strategy that integrates community engagement, shareholder inclusiveness, and the creation of dynamic workplaces with their core business objectives.